Flavobacterium sp. strain GJW24 ameliorates drought resistance in Arabidopsis and Brassica - Kim, Hani; Woo, Og-Geum; Kim, Ji Bin; Yoon, So-Young; Kim, Jong-Shik; Sul, Woo Jun; Hwang, Jee-Yeon; Lee, Jae-Hoon (Frontiers in Plant Science, 2023)
Candidate strains that contribute to drought resistance in plants have been previously screened using approximately 500 plant growth-promoting rhizobacteria (PGPR) obtained from Gotjawal, South Korea, to further understand PGPR associated with plant drought tolerance. In this study, a selected PGPR candidate, Flavobaterium sp. strain GJW24, was employed to enhance plant drought tolerance. GJW24 application to Arabidopsis increased its survival rate under drought stress and enhanced stomatal closure. Furthermore, GJW24promoted Arabidopsis survival under salt stress, which is highly associated with drought stress. GJW24 ameliorated the drought/salt tolerance of Brassica as well as Arabidopsis, indicating that the drought-resistance characteristics of GJW24 could be applied to various plant species. Transcriptome sequencing revealed that GJW24 upregulated a large portion of drought-and drought-related stress-inducible genes in Arabidopsis. Moreover, Gene Ontology analysis revealed that GJW24-upregulated genes were highly related to the categories involved in root system architecture and development, which are connected to amelioration of plant drought resistance. The hyper-induction of many drought/saltresponsive genes by GJW24 in Arabidopsis and Brassica demonstrated that the drought/salt stress tolerance conferred by GJW24 might be achieved, at least in part, through regulating the expression of the corresponding genes. This study suggests that GJW24 can be utilized as a microbial agent to offset the detrimental effects of drought stress in plants.